Mechanical Performance of Deep Circular Caisson Sinking in Deep Layered Soft Soil. (25th August 2022) - Liu, Mingqing; Sun, Fuxue; Gan, Qinyu; Chi, Enan; Li, Xiaochun; Ge, Gang
Abstract : In order to study the mechanical behavior of open caisson foundation in the Wenzhou area, combined with the characteristics of the soil layer in the Wenzhou area, based on the field measurement and investigation of a wide range of engineering cases, this project studies the mechanical properties of open caisson sinking in soft soil stratum and optimizes the construction parameters through the combination of field measurement, numerical simulation, and theoretical calculation, while ensuring the smooth sinking of the open caisson, control the deformation effect of the soil around the open caisson to serve the urban construction. The research results can directly serve the whole process of design, construction, measurement, and control of open caisson engineering. It has engineering practical significance and can be used as a reference for similar projects.